A refined diffuse cohesive approach for the failure analysis in quasibrittle materials—part I: Theoretical formulation and numerical calibration. Issue 2 (6th August 2019) - De Maio, Umberto; Greco, Fabrizio; Leonetti, Lorenzo; Luciano, Raimondo; Nevone Blasi, Paolo; Vantadori, Sabrina
Abstract: In this work, a refined interelement diffuse fracture theoretical model, based on a cohesive finite element approach, is proposed for concrete and other quasibrittle materials. This model takes advantage of a novel micromechanics‐based calibration technique for reducing the artificial compliance associated with the adopted intrinsic formulation. By means of this technique, the required values for the elastic stiffness parameters to obtain nearly invisible cohesive interfaces are provided. Furthermore, the mesh‐induced toughening effect, essentially related to the artificial crack tortuosity caused by the different orientations of the interelement cohesive interfaces, is numerically investigated by performing comparisons with an additional fracture model, newly introduced for the purpose of numerical validation. These comparisons are presented to assess the reliability and the numerical accuracy of the proposed fracture approach.